2006
DOI: 10.1002/marc.200500852
|View full text |Cite
|
Sign up to set email alerts
|

Thermal and Surface Properties of Phenolic Nanocomposites Containing Octaphenol Polyhedral Oligomeric Silsesquioxane

Abstract: We have synthesized a new polyhedral oligomeric silsesquioxane (POSS) containing eight phenol functional groups and copolymerized it with phenol and formaldehyde to form novolac-type phenolic/POSS nanocomposites exhibiting high thermal stabilities and low surface energies. Our DSC results indicate that the glass transition temperature of these nanocomposites increased initially upon increasing their POSS content, but then decreased at POSS content above 10 wt.-%, presumably because of the formation of relative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
70
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 89 publications
(74 citation statements)
references
References 23 publications
4
70
0
Order By: Relevance
“…[1][2][3][4] It has been demonstrated that poly(4-vinyl pyridine) (P4VP) is able to interact strongly with polymers of a wide variety of structures through hydrogen bonding, such as poly(vinyl phenol) (PVPh), [5][6][7][8] poly(vinyl alcohol), [9] and phenolic resin. [10] It is well known that the nature of the solvent medium can control complex formation.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] It has been demonstrated that poly(4-vinyl pyridine) (P4VP) is able to interact strongly with polymers of a wide variety of structures through hydrogen bonding, such as poly(vinyl phenol) (PVPh), [5][6][7][8] poly(vinyl alcohol), [9] and phenolic resin. [10] It is well known that the nature of the solvent medium can control complex formation.…”
Section: Introductionmentioning
confidence: 99%
“…Novolac-type phenolic/POSS nanocomposites with high thermal stabilities and low surface energies were prepared by POSS containing eight phenol functional groups, phenol, and formaldehyde. 14 Here, we report a new hybrid PPM presenting POSS units in their side chains. We incorporated the POSS units into PPM to improve its thermal stability and a uniform distribution of polymer particles.…”
mentioning
confidence: 93%
“…14,15 Organic groups are introduced into the molecule either directly, during the synthesis or by a transformation of existing groups. 16 Over the last years, researchers have made a library of functionalized POSS compounds such as octaphenols, 17 octaisocyanates, 18 oligoethylene oxides, 19 and liquid crystalline materials.…”
Section: Introductionmentioning
confidence: 99%